Analisis Bauran Pemasaran Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Chips-Chips Lumer - Poluan, Adella Neuville Hefly; Hartiati, Amna; Wiranatha, Anak Agung Putu Agung Suryawan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
The Chips-Chips Lumer product is an innovative product produced by Pak Eko's Cheese Banana MSMEs which has been marketed since August 2023. The purpose of this study is to determine the effect of the marketing mix on customer loyalty through customer satisfaction for Chips-Chips Lumer products. In addition, this study also provides recommendations for improvement to related businesses. This research is supported by literature study, interviews with the owner of Pak Eko Cheese Banana business, and distributing questionnaires to 80 respondents. Data analysis used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results showed a significant effect of the marketing mix on customer satisfaction with a direct effect of 82% and then a significant effect of 77% on customer loyalty. The customer satisfaction variable did not succeed in becoming a mediating variable between the influence of the marketing mix on customer loyalty because it produced an insignificant effect.